P273 Assessment Of Lung Microstructure In Interstitial Lung Disease With Hyperpolarised Gas Mri. (10th November 2014) - Stewart, NJ; Norquay, G; Parra-Robles, J; Marshall, H; Leung, G; Murphy, PS; Schulte, RF; Elliot, CA; Condliffe, R; Billings, CG; Smith, I; Griffiths, PD; et al.
Abstract : Introduction and objectives: Magnetic resonance (MR) imaging of the hyperpolarised noble gases 3 He and 129 Xe provides exquisite depiction of pulmonary ventilation. In addition, MR measurement of the apparent diffusion coefficient (ADC) of 3 He gas has proven clinical utility in assessment of emphysema. Furthermore, xenon is soluble and is a promising marker of pulmonary gas-exchange. The motivation of this work was to demonstrate non-invasive quantification of whole-lung septal thickness (ST) and helium ADC in subjects with idiopathic pulmonary fibrosis (IPF) and systemic sclerosis (SSc) using 129 Xe and 3 He MR. Methods: Hyperpolarised 129 Xe spectroscopy was performed on ten healthy volunteers (23–74 yrs), four subjects with SSc and four with IPF at 1.5 T. A chemical shift saturation recovery (CSSR) method was used to assess the dynamics of xenon uptake into parenchymal tissues and blood and to derive quantitative information about lung microstructure. From the subject cohort, six volunteers and seven patients were also scanned at 1.5 T with a diffusion-weighted sequence to determine 3 He ADC values. For comparison with MR experiments, standard pulmonary function tests including the diffusing capacity of carbon monoxide (DLCO ) were performed. Results: Pulmonary function was significantly worse in both SSc and IPF subjects than healthy volunteers (DLCO < 45% in IPF patients). Both 129 Xe CSSR ST and 3 He ADC values were elevated in subjects with SSc, and to a larger degree in those with IPF, compared with healthy volunteers (Figure 1, top). These two MR metrics correlated significantly, suggesting that fibrotic remodelling of tissue both degrades gas-exchange efficiency and induces alveolar widening causing less-restricted gas diffusion (although emphysema was reported for only one subject on CT). The 129 Xe CSSR-derived ST values correlated well with whole-lung DLCO (Figure 1, bottom) and in healthy volunteers, ST increased with age (p < 0.05). Conclusions: Hyperpolarised 129 Xe and 3 He MR techniques are sensitive to small changes in gas-exchange efficiency and alveolar surface geometry, respectively. These two factors appear to have an intrinsic link, identified in the presence of fibrotic lung disease without obvious emphysema. Further application of these MR techniques may prove useful in the diagnosis/assessment of different forms of ILD.